Simulations of low and high solid flux risers using energy minimization multiscale model: Effect of cluster diameter correlations - Shah, Milin; Utikar, Ranjeet; Tade, Moses; Pareek, Vishnu (2011)
Accounting an effect of cluster formation on hydrodynamics of FCC riser is critical, and the energy minimization multiscale (EMMS) model provides a framework to capture clusters by using a cluster diameter correlation. In this study, different cluster diameter correlations (CDC) were used with the EMMS model to calculate structure-based drag coefficients, and these drag coefficients were then used to carry out CFD simulations of 2D riser with both low and high flux flows of FCC particles. Initial simulations using the EMMS and Gidaspow drag model showed that the EMMS model could capture an S-shape axial profile with a dense bottom and dilute top with showing qualitative agreements with experimental data. The EMMS drag largely depends on a cluster diameter correlation. Therefore, simulations were performed using the EMMS drag coefficients calculated from different CDCs i.e. (i) Chavan, (1984), (ii) Harris et al., (2002) and (iii) Subbarao, (2010). It was found that the cluster diameter correlations had considerable effect on the calculated drag and hydrodynamic predictions. While no universal agreement was observed between the hydrodynamic prediction from different CDCs and experimental data. Thus, it was concluded that a combination of CDCs in different ranges of voidages can be useful to achieve qualitative agreements between the hydrodynamics predictions and experimental data, and this study can be used to identify possible this combination of the CDCs for a given flow system.